Adipose-Derived Stem Cells Based on Electrospun Biomimetic Scaffold Mediated Endothelial Differentiation Facilitating Regeneration and Repair of Abdominal Wall Defects via HIF-1α/VEGF Pathway - Dong, Wenpei; Song, Zhicheng; Liu, Suihong; Yu, Ping; Shen, Zhipeng; Yang, Jianjun; Yang, Dongchao; Hu, Qinxi; Zhang, Haiguang; Gu, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Application of synthetic or biological meshes is the main therapy for the repair and reconstruction of abdominal wall defects, a common disease in surgery. Currently, no ideal materials are available, and there is an urgent need to find appropriate ones to satisfy clinical needs. Electrospun scaffolds have drawn attention in soft tissue reconstruction. In this study, we developed a novel method to fabricate a composite electrospun scaffold using a thermoresponsive hydrogel, poly (N-isopropylacrylamide)-block-poly (ethylene glycol), and a biodegradable polymer, polylactic acid. This scaffold provided not only a high surface area/volume ratio and a three-dimensional fibrous matrix but also high biocompatibility and sufficient mechanical strength, and could simulate the native extracellular matrix and accelerate cell adhesion and proliferation. Furthermore, rat adipose-derived stem cells (ADSCs) were seeded in the composite electrospun scaffold to enhance the defect repair and regeneration by directionally inducing ADSCs into endothelial cells. In addition, we found early vascularisation in the process was regulated by the hypoxia inducible factor-1α (HIF-1α)/vascular endothelial growth factor (VEGF) pathway. In our study, overexpression of HIF-1α/VEGF in ADSCs using a lentivirus system promoted early vascularisation in the electrospun scaffolds. Overall, we expect our composite biomimetic scaffold method will be applicable and useful in abdominal wall defect regeneration and repair in the future.